Disability sport - DePauw, Karen P.; Gavron, Susan J. 1947- (Human Kinetics, 2005)
Disability Sport, Second Edition, provides a comprehensive and practical look at the past, present, and future of disability sport. Topics covered are inclusive of youth through adult participation with in-depth coverage of the essential issues involving athletes with disabilities. This new edition has updated references and new chapter-opening outlines that assist with individual study and class discussions. The book contains an up-to-date and comprehensive synthesis of information on disability sport in its historical context; organizations, competitions, and sport opportunities for athletes with disabilities; international perspectives; and coaching and training of athletes with disabilities, including sports medicine issues, activity modifications, equipment uses, and event management for both adults and children. In addition, the book addresses current challenges and controversies in disability sport (e.g., inclusion and integration, classification, ethics issues, doping, and equity issues) and looks into the future of disability sport. It includes minibiographies of standouts in disability sport from around the world. Students and professionals can use Disability Sport, Second Edition, as a springboard to further research; as an up-to-date reference; and as a tool in working with, or preparing to work with, athletes with disabilities.